Dynamic mode decomposition and reconstruction of transient cavitating flows around a Clark-Y hydrofoil. Issue 5 (July 2020) - Qiu, Rundi; Huang, Renfang; Wang, Yiwei; Huang, Chenguang
HIGHLIGHTS: Dynamic mode decomposition (DMD) is applied in unsteady cavitating flow. The frequencies of cavitating flow are extracted to analyze the characteristic of cavitating flow. The velocity field of cavitating flow is reconstructed with high accuracy using less information. Abstract: The transient cavitating flow around the Clark-Y hydrofoil is numerically investigated by the dynamic mode decomposition with criterion. Based on the ranking dominant modes, frequencies of the first four modes are in good accordance with those obtained by fast Fourier transform. Furthermore, the cavitating flow field is reconstructed by the first four modes, and the dominant flow features are well captured with the reconstructed error below 12% when compared to the simulated flow field. This paper offers a reference for observing and reconstructing the flow fields, and gives a novel insight into the transient cavitating flow features.